Crew cutting into rock face of Slippery Rock, Tunnel Mountain during the construction of the White Pass & Yukon Railroad, Alaska, 1898. - Barley, H. C.
Caption on image: "Cutting grade on Tunnel Mountain near White Pass." The men were held to the rock face by ropes. PH Coll 246.142 See also PH Coll 296.14 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number